Social capital in successful sustainable rural development enterprises - Román Arredondo, Patricia; Hernández Juárez, Martín; León Merino, Aurelio; Sangerman- Jarquín, Dora María (Revista Mexicana de Ciencias Agrícolas, 2017)
Rural enterprises are entities that contribute to the  generation of jobs and income in the rural sector. To this  end, rural families have developed various community- based initiatives to better leverage their limited resources  or to efficiently link to different levels of structures  and processes individually and collectively to operate  successfully. However, there are studies that indicate that  more than half of the start-up companies have not had  the expected success and tend to disappear (World Bank,  2007), which is due to factors related to deficiencies in the  organization, limitations in interpersonal relationships,  internal conflicts and mistrust among others (Acuña,  2011; Toiber, 2016; Díaz  et al ., 2016). The objective of  this research was to identify the role of social capital  elements as well as the material and non-material benefits  derived from this operation process of the companies  of the Red Nacional de Desarrollo Rural Sustentable  (RENDRUS). The research was conducted in 2016, with  a mixed approach, data were obtained from a survey and  open interview applied to 20 RENDRUS representatives.  The results show that the existence of social capital allows  companies to obtain various material and non-material  benefits that positively influence their success.
Keywords: RENDRUS rural enterprises, social capital, tangible and intangible benefits